Use of virtual reality in digital marketing communication - Łysik, Łukasz; Łopaciński, Karol (Wykorzystanie wirtualnej rzeczywistości w cyfrowej komunikacji marketingowej, 2019)
The practical utility of many VR instruments and tools has been recognized by marketing specialists – the rapid development of marketing approaches based on VR solutions is a good example of this trend and seems to offer the promise of a much wider application of VR in this context. Virtual reality is generally considered as one of the most promising technologies of the future, with enormous potential to influence the customer experience. This study presents an attempt at determining the effective impact of virtual reality upon marketing activities and its potential to influence and shape modern consumer behaviour. These objectives were addressed on the basis of literature studies and analytical evaluations of selected case studies involving the application of VR technologies in marketing. This paper constitutes an introductory chapter in a broader series of studies devoted to the examination of VR properties, the role of VR in the formulation of new paradigms in the realm of marketing, and the analytical evaluation of modern consumer behaviour
Informatyka Ekonomiczna = Business Informatics, 2019, Nr 4 (54), s. 29-45
Keywords: informatyka ekonomiczna